Management of the financial tasks of liquor producing companies: A view from social responsibility (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2025)
This essay aims to carry out a hermeneusis of the management of financial activities from the perspective of Corporate Social Responsibility in liquor producing companies specifically: Sucesora de Ramón R. Leal y Cía. C.A. Under a methodology aligned with the interpretive paradigm, with an ontoepistemic stance of multiple reality, constructed in a subjective manner, leading to a conception of qualitative elements in the elucidation and hermeneusis of reality. Theoretical references related to management and administration, behavioral finance and social responsibility were used. The understanding of these categories allows us to know the qualities and opportunities for improvement from the holistic organizational vision, pointing towards a paradigmatic break in favor of the birth of the new reality, leveraged on a recognition as a socially responsible company, based on the need to actively participate in a context with evolved demands, especially in the social field. When speaking of a socially responsible management, this understanding is supported by the concept of stakeholders, collaborators who have a high level of importance for the new management, triggering a success factor for the organization.
Keywords: behavioral finance; management; social responsibility